UNINTENTIONAL MONOTHERAPY IN RHEUMATOID ARTHRITIS PATIENTS RECEIVING TOFACITINIB AND DRUG SURVIVAL RATE OF TOFACITINIB - Inanc, N.; Abacar, K.; Ozturk, M. A.; Tufan, A.; Karadeniz, H.; Sari, I.; Onen, F. (Elsevier, 2022)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 01-04, 2022 -- Copenhagen, DENMARK